Determinan manajemen diare pada balita di Indonesia - Salma, Tazkiya Tsabita; Santik, Yunita Dyah Puspita (Poltekkes Kemenkes Aceh, 2024)
Background: Diarrhea is ranked second as a cause of death in children under five with a mortality rate reaching 370.000 children in the world in 2019. The worst complication of diarrhea in children under five that is not treated immediately is dehydration which can lead to death. The impact when diarrhea in children under five is not treated besides it can cause dehydration complications can also interfere with child growth which is the main cause of malnutrition.Objectives: To find out the factors related to diarrhea management in children under fives in Indonesia.Methods: This study used a cross-sectional design with a sample of 1819 mothers who have children under five diarrhea with complete data. The study was conducted using secondary data from Indonesian Demographic Health Survey (IDHS) 2017 collected using questionnaires. Data were analyzed using Chi-Square bivariate test and logistic regression multivariate test. The results of statistical tests are categorized as significant if they have p<0,05.Results: The bivariate test showed variables of children under five sex (p=0,026), maternal occupation (p=0,040), and knowledge related to ORT (p=0,000) has a relationship with diarrhea management in children under fives. After controlling for other variables using logistic regression tests, the results showed the sex variable of children under fives with a value of p = 0,018 and PR = 1,43 (95% CI = 1,06-1,92), maternal working status with values p=0,028 and PR=1,38 (95% CI=1,04-1,85), and knowing/using ORT with values p=0,000 and PR=2,56 (95% CI= 1,61-4,18) being a variable that affects the management of diarrhea in children under fives.Conclusion: There is a relationship between the gender of the children under five, the working status of the mother, and knowledge or having used ORT and having a children under five with diarrhea has a relationship with the management of diarrhea in children under fives so it is necessary to intensify education and programs related to the management of diarrhea in children under fives to increase maternal knowledge.KeywordsDiarrhea, management, children under five, demograhic and health surveys